Subtotal petrosectomy: Surgical technique, indications, outcomes, and comprehensive review of literature - Prasad, Sampath Chandra; Roustan, Valeria; Piras, Gianluca; Caruso, Antonio; Lauda, Lorenzo; Sanna, Mario (The Laryngoscope, 2017)
To describe the technique of subtotal petrosectomy (STP), to analyze the outcomes, and to review the literature STUDY DESIGN: A retrospective review. Four hundred sixty cases of STP performed for various indications were included in the study, which was conducted at a quaternary referral center for otology and skull base surgery. Surgical and audiological parameters, and complications were evaluated. Our results were compared with the existing literature on the subject. Two hundred ninety-seven (64.6%) patients had been subjected to multiple surgeries before an STP was performed. The most common indication for STP was recurrent chronic otitis with or without cholesteatoma, with 165 (35.9%) patients. Difficult cases of cochlear implantation, temporal bone fractures, and class B3 tympanomastoid paragangliomas were the next most common indications, with 91 (19.8%), 43 (9.4%), and 38 (8.3%) cases, respectively. The median follow-up of the patient pool was 36 ± 19 months. Recidivism and postauricular wound fistula were the most common complications, seen in five (1.1%) patients each. This series of STP is the largest reported in the literature CONCLUSIONS: STP is a very useful and safe surgical tool in the management of a variety of problematic situations in otology, as it offers the possibility of a definitive cure by offering radical clearance. This procedure can be combined safely with hearing implantation procedures. 4. Laryngoscope, 127:2833-2842, 2017.